(untitled) (Research, Society and Development, 2023)
Introduction: Glaucoma is an ocular pathology that causes damage to the optic nerve and decreased visual acuity, with the main risk factor being increased intraocular pressure. Objective and Methods: To provide, through a narrative bibliographic review, a broad approach, which will encompass aspects such as definition, classification, pathophysiology, clinical picture, diagnostic and treatment methods. Results and Discussion: Glaucoma is a disease that compromises the quality of life of affected patients, whether significantly or not, therefore, in order for there to be a good therapeutic response, and a better prognosis in cases, the diagnosis of this pathology in stages initial assessments, as well as the identification of risk factors by the doctor, if necessary.